STUDY ON THE INVOLVEMENT OF THE UNIVERSITY IN TRAINING AND LIFELONG LEARNING OF THE HIGH SCHOOL’S GRADUATES - PARVU, Iulia; GRECU, Iulia; MITRAN, Paula-Cornelia; GRECU, Gheorghe (Annals of Spiru Haret University. Economic Series, 2018)
The nowadays continuously expansion of the market for higher education services puts a high pressure on the management of such institutions. Universities are trying to keep their position on the market by applying theories and practices that have traditionally been used by the business environment. This paper proposes to adapt such a practice to higher education institutions. This is the strategy of backward vertical integration. We understand this by highlighting the possibilities that higher education institutions have to take over some of the activities carried out in high schools. Starting from the experience of a project to whose implementation the authors participated, the paper describes how the counseling and vocational guidance activities addressed to high school students can be carried out by the higher education institutions.